2020
DOI: 10.22541/au.160466945.56576285/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plant Hormone-Mediated Regulation of Stress Responses in Fruit Crops- A Review

Abstract: One of the challenges facing fruit crop production globally is the regional climate regimes are becoming more unpredictable year after year leading to various type of stress. The exact impact of these stress on fruit crops is difficult to predict. Plant hormones can improve tolerance against abiotic stresses by inhibiting or reducing the active oxygen (AOS) accumulation, electrolyte leakage, induce the expression of stress-specific genes, etc. Among the major hormones produced by the plants, ABA, SA, JA and ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 152 publications
0
2
0
Order By: Relevance
“…Plant growth-regulating hormones such as abscisic acid (ABA), ethylene, jasmonic acid, and salicylic acid (SA) play a significant role during abiotic stresses, including cold, salinity, drought, light, and heavy metal stresses and they acts as links between stress regulator and responses at cellular, tissue and organ level to external stimuli ( Rachappanavar et al., 2022 ). When Vitis vinifera cv.…”
Section: Signaling and Molecular Responsesmentioning
confidence: 99%
“…Plant growth-regulating hormones such as abscisic acid (ABA), ethylene, jasmonic acid, and salicylic acid (SA) play a significant role during abiotic stresses, including cold, salinity, drought, light, and heavy metal stresses and they acts as links between stress regulator and responses at cellular, tissue and organ level to external stimuli ( Rachappanavar et al., 2022 ). When Vitis vinifera cv.…”
Section: Signaling and Molecular Responsesmentioning
confidence: 99%
“…To eliminate the effects of biotic and abiotic stresses, plants have developed several mechanisms, including the responsive action of stress-regulating genes for the plant’s growth and maintenance [ 4 ]. Plants mediate the early stress response by the regulation of phytohormones, such as jasmonic acid (JA), abscisic acid (ABA), and salicylic acid (SA) [ 5 , 6 ]. Various transcription factor proteins have also been identified that play a key role in the regulation of gene expression by interacting with cis -regulatory promoter elements at the transcription level [ 7 ].…”
Section: Introductionmentioning
confidence: 99%